Biochemical purification and characterization of a truncated acidic, thermostable chitinase from marine fungus for N-acetylglucosamine production - He, Bin; Yang, Liyan; Yang, Dengfeng; Jiang, Minguo; Ling, Chengjin; Chen, Hailan; Ji, Feng; Pan, Lixia (Frontiers in Bioengineering and Biotechnology, 2022)
N-acetylglucosamine (GlcNAc) has been broadly used in nutritional supplement for helping joint health and treating osteoarthritis, which are commonly prepared from chitin with chitinases. So far, while most GlcNAc is prepared from colloidal chitin, chitinases used in preparing GlcNAc are essential to be acidic enzyme. Herein, we characterized an acidic, highly salinity tolerance and thermostable chitinase AfChiJ, which was identified from the marine fungi Aspergillus fumigatus df673, with an ability to degrade chitin into GlcNAc. Based on the AlphaFold2 structure prediction, a truncated Δ30AfChiJ was heterologously expressed in E. coli and successfully purified. Meanwhile, it was characterized that it is active on colloidal chitin, with optimal temperature of 45C, optimal pH of 4.0 and optimal salt concentration of 3% NaCl. It is stable over a broad pH range of 2.0-6.0 below 45C and maintained high activity (≥97.96%) in 1%-7% NaCl. Moreover, we observed a significant increase in chitinase activity of Δ30AfChiJ through the addition of Mg2+, Ba2+ , urea (10 mM and 50 mM) as well as chloroform (10% and 20%). When acting on colloidal chitin, the main product is GlcNAc. Enzyme substrate property assay combined the results of molecular docking and sequence alignment of homologous proteins showed AfChiJ is an exochitinase contained both chitobiosidases and N-acetylglucosaminidase property at the same time. Our results suggest that AfChiJ likely has potential in conversion of marine debris and chitin-containing biomass into high-value added GlcNAc.